Graduate and Employer Satisfaction as Indicators of Higher Education Service Quality - Lailatul Hidayah Ayu Putri; Fretty Fajarwati; Afifah Umudini (Universitas Nurul Jadid, 2025)
This study aims to analyze the satisfaction levels of graduates and graduate users with higher education services as an indicator of institutional service quality. A qualitative approach, employing a survey method, was used, involving two main respondent groups: graduates from various study programs and graduate users from government, private, and industrial sectors. The primary instrument was a Likert 1–4 scale satisfaction questionnaire, complemented by open-ended questions to explore respondents' experiences and perceptions in depth. Data were analyzed using descriptive statistics and thematic analysis. The results indicate that satisfaction levels across all faculties were high (mean > 3.80), with the Midwifery Study Program recording the highest score (4.00) and the PG PAUD Study Program the lowest (3.81), though still within the satisfied category. Lecturer ethics and learning quality received the highest ratings from graduates, while laboratory facilities received the lowest. For graduate users, discipline and work ethic scored highest, whereas mastery of information technology was relatively lower. These findings confirm that academic services and soft skills are strong; however, improvements in technological facilities and competencies are necessary to enhance graduate competitiveness further.